(untitled) (CIPEEX, 2022)
THE ACT OF PERCEIVING SOMETHING CAN END IN TAKING ACTION. THIS WORK AIMS TO CREATE A PLATFORM TO PROVIDE WEATHER AND CLIMATE DATA, COLLECTING DATA FROM A METEOROLOGICAL STATION IN THE CITY OF ANÁPOLIS GO. THE DATA WERE SELECTED AND EVALUATED TO GENERATE PANELS THAT CONTAIN FRIENDLY AND INTELLIGENT INFORMATION. THERE ARE CURRENTLY SEVERAL SERVICES AVAILABLE FOR MAKING DATA AVAILABLE ON THE INTERNET, THE SO-CALLED DASHBOARDS. ONE OF THE OBJECTIVES WAS TO CREATE AWARENESS AMONG USERS REGARDING ENVIRONMENTAL PRESERVATION. THE ACT OF VISUALIZING AND TRACKING TIME ON A PLATFORM THAT AT THE SAME TIME DENOTES ENVIRONMENTAL EDUCATION. TO CARRY OUT THE WORK, THE FOLLOWING STEPS WERE CARRIED OUT: 1) PREPARATION OF STATION DATA IN THE LAST FOUR YEARS; 2) SELECTION OF AUTOMATIC PANEL PROGRAMS AVAILABLE ON THE INTERNET (DASHBOARDS) 3) TEST WITH THE CHOSEN PLATFORM 4) CREATION OF A TEST SITE FOR HOSTING.